Enterprise business portals II with IBM tivoli access manager - Bücker, Axel (IBM redbooks, 2003)
Mastering IBM Tivoli Access Manager is a very important factor in successfully deploying contemporary e-business solutions. Access Manager is the key element in an e-business security framework that needs thorough understanding to achieve maximum security, functionality, and performance. Based on expandable security policies for users, groups, and protected resources, Tivoli Access Manager manages authentication and authorization for application servers, Web sites, and virtually any other resource that requires protection, including custom-written applications. This IBM Redbooks publication describes how to build an integrated enterprise business portal with Tivoli Access Manager Version 4.1, WebSphere Portal, mySAP Workplace, and the SAP Enterprise Portal. It also describes how to implement a federated single sign-on solution within a Web Services scenario. This book is partitioned into general and customer scenario based sections. This book is a valuable resource for security administrators and architects who wish to understand and implement a centralized security infrastructure. Please note that the additional material referenced in the text is not available from IBM.